2006
DOI: 10.1002/j.2168-9830.2006.tb00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Survey to Assess K‐12 Teachers' Perceptions of Engineers and Familiarity with Teaching Design, Engineering, and Technology

Abstract: This paper describes the development of a survey instrument to assess K-12 teachers' perceptions of engineering and their familiarity with teaching design, engineering, and technology (DET). Item development, field testing, and the factor analysis are described along with reliability and validity. Administration of the instrument revealed differences based on gender, grade level taught, and years of teaching experience. Female teachers rated the importance of DET higher than male teachers, elementary teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
1
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 15 publications
5
145
1
3
Order By: Relevance
“…Yasar, Baker, Robinson-Kurpius, Krause, and Roberts (2006) developed a questionnaire that explored general beliefs and interest of K-12 teachers concerning engineering education. Yasar et al (2006) explored four different sets of beliefs about engineering education: (a) the importance of engineering education, (b) familiarity with engineering education, (c) stereotypical characteristics of engineers, and (d) characteristics of engineering. Essentially, they found that teachers valued engineering education, were not very familiar with it, leaned toward some stereotypic beliefs, and generally knew characteristics of engineering.…”
Section: Teacher Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Yasar, Baker, Robinson-Kurpius, Krause, and Roberts (2006) developed a questionnaire that explored general beliefs and interest of K-12 teachers concerning engineering education. Yasar et al (2006) explored four different sets of beliefs about engineering education: (a) the importance of engineering education, (b) familiarity with engineering education, (c) stereotypical characteristics of engineers, and (d) characteristics of engineering. Essentially, they found that teachers valued engineering education, were not very familiar with it, leaned toward some stereotypic beliefs, and generally knew characteristics of engineering.…”
Section: Teacher Efficacymentioning
confidence: 99%
“…Although the present authors have some concerns over the nature of some of the scales, it can nevertheless be reasonably inferred that teachers value engineering education, but do not know much about it. Unlike Yasar et al's (2006) more general approach, the present investigation examines more specific beliefs about learning outcomes that an actual engineering middle school curriculum is attempting to inculcate in two schools.…”
Section: Teacher Efficacymentioning
confidence: 99%
“…This level of innovation entails great challenges in preparing elementary teachers because ''the education of the vast majority of elementary school teachers (such as the bulk of our population) did not include engineering or technology activities or information'' (Cunningham et al, 2006, p. 1). The challenge of preparing elementary teachers for engineering teaching also lies in the fact that elementary teachers are generally disinterested in and intimidated by science content (Buczynski & Hansen, 2010) and by DET (Yasar et al, 2006). In addition, it has been shown that engineering teaching has its idiosyncratic properties rendering generic teaching strategies ineffective (Strobel & Sun, 2013).…”
Section: Preparing Elementary Teachers For Teaching Engineeringmentioning
confidence: 99%
“…However, engineering is not a discipline traditionally taught at the elementary level, and elementary teachers, in comparison to middle and high school teachers, are the least prepared for and least interested in teaching design, engineering, and technology (DET) (Yasar, Baker, Robinson-Kurpius, Krause, & Roberts, 2006). There is an urgent need to prepare elementary teachers to teach engineering.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yasar and colleagues found that (a) K-12 teachers held stereotypical views of engineers, (b) elementary teachers placed less value on teaching engineering design than secondary teachers do, and (c) teachers, in general, lacked confidence in the abilities to teach engineering design activities. 13,14 Further, the limited available research indicates that elementary teachers report feeling unprepared to teach engineering practices. 15,16 Below we explore these interrelated challenges to teacher professional development in engineering education, as well as some challenges uniquely faced by teachers in rural schools.…”
Section: Related Literaturementioning
confidence: 99%